2022
DOI: 10.2147/jpr.s385228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ferroptosis-Related Molecular Subtypes with Immune Infiltrations in Neuropathic Pain

Abstract: Background Neuropathic pain (NP) caused by a lesion or disease of the somatosensory nervous system is a common chronic pain condition that has a major impact on quality of life. However, NP pathogenesis remains unclear. The purpose of this study was to identify differentially expressed genes (DEGs) and specific and meaningful gene targets for the diagnosis and treatment of NP. Methods Data from rat spinal nerve ligations and the sham group were downloaded from the Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…GSEA is used to evaluate the distribution trend of genes from a predefined gene set in the gene list ranked with phenotypic relevance, to judge its contribution to phenotype 21 . We used the R packages limma, org.…”
Section: Gene Set Enrichment Analysis (Gsea) Between Ad and Normal Gr...mentioning
confidence: 99%
“…GSEA is used to evaluate the distribution trend of genes from a predefined gene set in the gene list ranked with phenotypic relevance, to judge its contribution to phenotype 21 . We used the R packages limma, org.…”
Section: Gene Set Enrichment Analysis (Gsea) Between Ad and Normal Gr...mentioning
confidence: 99%
“…It has been shown that reactive oxygen species (ROS) and oxidative stress are involved in the development of NP. Under normal physiological conditions, intracellular antioxidants are in dynamic balance with intracellular ROS ( Bi et al, 2022 ). When mitochondrial damage occurs, ROS production is significantly higher compared to normal physiological levels.…”
Section: Introductionmentioning
confidence: 99%
“…When mitochondrial damage occurs, ROS production is significantly higher compared to normal physiological levels. And endogenous antioxidants are severely depleted, resulting in a disruption of the balance, leading to intracellular oxidative stress ( Bi et al, 2022 ). Reactive oxygen species scavengers can alleviate NP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation